Problematics of Domestic Violence Case Handling of PPA Unit of Pangkalpinang Police: Analysis of Case Arrears - Dewi Lestari; Enny Agustina (Journal of Law, Politic and Humanities, 2025)
This research examines the problems in handling Domestic Violence (KDRT) cases at the Women and Children Protection Unit (PPA) of the Pangkalpinang City Police, with a focus on the backlog of cases that occurred during the 2021-2023 period. This study aims to identify the factors causing the backlog of KDRT cases and analyze its implications for the performance of the PPA Unit. The research method used is empirical legal research with a qualitative approach, through in-depth interviews, document studies, and observations. The results show that the backlog of cases is caused by three main factors: the uncooperative behavior of victims, limitations in tracing perpetrators, and institutional resource constraints. The implications of the case backlog include a decrease in the effectiveness of case handling, psychological pressure on personnel, a decrease in public trust, and obstacles in inter-agency coordination. This study produces theoretical propositions in the form of "Integrated KDRT Case Management Theory" and "Integrated Case Management and Resource Optimization Theory" as solutions to address the problem of the KDRT case backlog.